Development of facetted platinum eletrocatalysts for low temperature fuel cell - Ramos, Silvina Gabriela (2018)
Fil: Ramos, Silvina Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Materiales de Misiones; Argentina.